2017
DOI: 10.1038/srep45172
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D both facilitates and attenuates the cellular response to lipopolysaccharide

Abstract: Vitamin D has a range of non-skeletal health effects and has been implicated in the response to respiratory infections. The aim of this study was to assess the effect of vitamin D on the response of epithelial cells, neutrophils and macrophages to lipopolysaccharide (LPS) stimulation. BEAS-2B cells (airway epithelial cell line) and primary neutrophils and macrophages isolated from blood samples were cultured and exposed to LPS with and without vitamin D (1,25(OH)2D). The production of IL-6, IL-8, IL-1β and TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 43 publications
2
40
0
2
Order By: Relevance
“…Pretreatment of macrophages with 1,25-VD 3 , or with its immediate precursor, 25-VD 3 , enhanced the LPS/ATP-induced macrophage activation ( Fig. 6 H ), consistent with previous findings ( 54 ).…”
Section: Resultssupporting
confidence: 92%
“…Pretreatment of macrophages with 1,25-VD 3 , or with its immediate precursor, 25-VD 3 , enhanced the LPS/ATP-induced macrophage activation ( Fig. 6 H ), consistent with previous findings ( 54 ).…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, there are some discrepancies existed with regard to the effect of calcitriol on NLRP3 inflammasome activation. Although calcitriol was proved to show inhibitory effects in autoimmunity related scenarios [17], [18], it was found to enhance IL-1β secretion during bacteria derived stimulation [20], [21] Similarly, calcitriol was shown to both facilitate and attenuate the production of IL-6, IL-8, IL-1β and TNFα in response to LPS stimulation in various cell types [22], [23]. Therefore, we proposed that the paradox of calcitriol might due to its multifunctional effects on both infection and chronic inflammation, and the impact of calcitriol on cytokine production by innate immune cells relies heavily on the cell that is producing the cytokine and the stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Parekh and colleagues analyzed the patient data of 61 patients with sepsis and utilized the CLP model, demonstrating that sepsis and severe sepsis are associated with vitamin D deficiency, which in turn is associated with more severe sepsis [49]. Accumulating evidence suggests that VD3 exerts protective effects during infections by up-regulating the expression of cathelicidin and beta-defensin 2 in phagocytes and epithelial cells [11]. In our study, we observed that VD3-pretreated mice had better survival after CLP and these mice also recovered faster with a better MSS score.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this natural compound may prove to be effective against sepsis, as an adjunct treatment modality. Previously, Chen and his colleagues suggested that VD3 exerts protective effects during infections by upregulating the expression of cathelicidin and beta-defensin 2 in phagocytes and epithelial cells [11]. Another study found that systemic LL-37 (human cathelicidin) levels may be regulated by VD3 status [12].…”
Section: Introductionmentioning
confidence: 99%